Improving the Passivation of Molybdenum Oxide Hole‐Selective Contacts with 1 nm Hydrogenated Aluminum Oxide Films for Silicon Solar Cells. Issue 15 (8th June 2020) - Gregory, Geoffrey; Feit, Corbin; Gao, Zhengning; Banerjee, Parag; Jurca, Titel; Davis, Kristopher O.
Abstract : The intrinsic and doped amorphous silicon layers in silicon heterojunction solar cells parasitically absorb light in the short wavelength region of the solar spectrum, lowering the generation current available to the device. Herein, a promising alternative to the hole‐selective amorphous silicon contact layers using only wide bandgap, transparent oxide materials is presented. Using thermal atomic layer deposition, a 1 nm hydrogenated aluminum oxide layer is deposited followed by a 4 nm molybdenum oxide layer on n‐type crystalline silicon. This contact stack provides an effective carrier lifetime of 1.14 ms. It is shown that the molybdenum oxide layer is successfully deposited with a high work function, which facilitates efficient hole extraction and repels majority carriers from the c‐Si surface. Then the implied open‐circuit voltage, saturation current density, and contact resistivity are recorded as a function of contact annealing temperature and show that they are relatively stable up to 200 °C. Abstract : A novel atomic layer deposition (ALD) process is introduced that incorporates additional hydrogen into 1 nm‐thick aluminum oxide surface passivation layers. These films yield effective carrier lifetimes above 1 ms, but are still thin enough to achieve low contact resistivity values when coupled with an ALD molybdenum oxide hole contact.